Numerical study on the smoke movement in office rooms with various exhaust vents settings. (2023) - Chiang Wong, Yeng; Chin Voon Sia, Charlie; Hing Chong, Kok; Rafiq Mirza Julaihi, Muhammad; Joseph, Annie
Abstract: The ventilation system is essential to maintain a high level of the smoke layer to improve visibility during a building fire. The high level of the smoke layer allows the nearby exits can be easily located, and the fire sources can be identified during the building fire and rescue. Hence, the study of smoke movement in building fires with exhaust vent settings is essential to improve fire safety in the building. In this study, the smoke movement in real-scale offices is numerically investigated by utilising the Large Eddy Simulation (LES) computational model. Six scenarios with various exhaust vents settings are considered. The temperature distribution and the smoke layer height in the four office rooms and lobby area are analysed for all the cases. Results confirmed that the temperature distribution and the layer height have no significant difference by increasing exhaust vent size. However, the upper wall-mounted exhaust vents provide an effective smoke exhaust system, significantly increasing the smoke layer height in all office rooms.